Do que “os Livros Diziam” à Rua da Glória, n. 52: o PCB e a “questão camponesa” (1927-1947) - dos Santos, Leonardo Soares (Universidade Federal Rural do Rio de Janeiro, 2015)
This article treat the formation of ““Peasantry Question” in the Communist Party of Brazil during 20 and 40’s. By this study is possible to perceive how ideas on men and situations of Brazilian hinterland to give place to Peasantry Leagues and formation of several formers strictly pointed towards to action in the country.